Social, Demographic, Economic and Geographical Conditions for the Budget Management in Poland - Abramczyk, Damian (Journal of Finance and Financial Law, 2018)
The basic task of households is spending and satisfying the needs of its users. Each of us, creates households, generates income for the family budget, regardless of age, gender, personal or health situation. Over the years, the process of managing incomes and expenses has evolved. Nowadays, these changes are very important in the era of general access to information. However, are we aware of changes in the structure of household budget management and its impact on society? The following article presents the structure of changes in managing the budget of households in demographic, economic, demographic and social terms based on statistical, empirical and available scientific literature. The following article presents the structure of changes in managing the budget of households in demographic, economic, demographic and social terms based on statistical, empirical and available scientific literature. The results of the Kronenberg Foundation's research at the Citi Handlowy bank will be presented, concerning the economic situation of households and Poles' attitudes towards finances. The most favorable option of managing the household budget will be selected and guidelines will be presented aimed at popularizing and streamlining the household budget management process.